Effects of large wood on invertebrate assemblages in the bed of a lowland river using a functional trait approach - Grabowski, Robert C.; Magliozzi, Chiara (Cranfield University, 2019)
This data is related to a research project using invertebrate ecological data to investigate functional traits at large wood sites. The research took place in the Hammer Stream, United Kingdom. The data was collected between 2016 and 2017 and available as separate .csv files.Two types of data are available: 1. Abundances of invertebrates and Traits2 Environmental dataPlease see the "description.txt" and 'readme.txt' files for further explanation
Keywords: macroinvertebrates'; 'hyporheos'; 'hyporheic zones'; 'meiofaunal community'; 'River ecology'; 'Large wood'; 'Community Ecology (excl. Invasive Species Ecology)'